2002
DOI: 10.1152/ajpregu.00181.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brain vasopressin and sodium appetite

Abstract: ventricular injections of vasopressin (VP) and antagonists with varying degrees of specificity for the VP receptors were used to identify the action of endogenous brain VP on 0.3 M NaCl intake by sodium-deficient rats. Lateral ventricular injections of 100 ng and 1 g VP caused barrel rotations and a dramatic decrease in NaCl intake by sodium-deficient rats and suppressed sucrose intake. 8 ]VP (MeT-AVP) significantly suppressed NaCl intake by sodium-deficient rats without causing motor disturbances. MeT-AVP had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…Mineralocorticoids have further been shown to upregulate Fos (41,42), angiotensin receptors (51), oxytocin receptors (51), vasopressin (20), and the vasopressin V 1a receptor (41,42). Vasopressin (11) and angiotensin II (9,29,45,50,51) in turn stimulate, whereas oxytocin (53) inhibits, salt intake. Interestingly, the effect of mineralocorticoids or salt depletion on salt appetite may be modified by glucocorticoids (18,34,50) and amphetamine (5).…”
Section: Discussionmentioning
confidence: 99%
“…Mineralocorticoids have further been shown to upregulate Fos (41,42), angiotensin receptors (51), oxytocin receptors (51), vasopressin (20), and the vasopressin V 1a receptor (41,42). Vasopressin (11) and angiotensin II (9,29,45,50,51) in turn stimulate, whereas oxytocin (53) inhibits, salt intake. Interestingly, the effect of mineralocorticoids or salt depletion on salt appetite may be modified by glucocorticoids (18,34,50) and amphetamine (5).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium depletion was induced by injections of furosemide (7.5 mg/kg, administered subcutaneously [sc]) and deoxycorticosterone acetate (DOCA, 5 mg/kg, sc) (Flynn et al 2005), followed 2 h later by an additional injection of 7.5 mg/kg furosemide (Tamura and Norgren 1997). Pilot studies indicated that this combination induced a more robust behavioral salt appetite than either single hormone alone in our lab and therefore the combination was selected for this electrophysiological and taste reactivity study (personal observations).…”
Section: Oral Infusion Testingmentioning
confidence: 99%
“…Rats were removed from the home cage, administered an intraventricular injection of angiotensin II (50 g/3 l; Sigma, St. Louis, MO), and returned to the cage. Water intake was measured for 20 min, and rats were determined to have correct placement of a patent cannula if they drank Ͼ5.0 ml of water following the angiotensin II injection (13,14). The experiments began 1-2 wk later.…”
Section: Surgerymentioning
confidence: 99%
“…In addition, the neurohypophyseal hormones, oxytocin and VP, are associated with the control of sodium balance (14). More specifically, many treatments that arouse the ingestion of sodium solutions also stimulate the release of VP into the blood (15,18,22,47,55).…”
mentioning
confidence: 99%